Interpreting Net Fiscal Incidence Calculations - Piggott, John; Whalley, John (The Review of Economics and Statistics, 1987)
This paper evaluates calculations of net fiscal incidence, using an applied general equilibrium model of Australia into which public goods are incorporated. Results indicate that it is inappropriate to regard the redistributive impacts of government policies as a zero sum game. For large reductions in public goods provision and taxes, the dominant effect is the foregone consumer surplus from suboptimal public goods provision. In addition, the redistributive pattern of small charges are quite different from large charges. Marginal and average net fiscal incidence, thus, need to be clearly separated, a point not emphasized in existing literature. Copyright 1987 by MIT Press.